Dr. Michael Mirzabeigi — Deep Plane Facelift — Atlanta - Mirzabeigi, Michael (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Michael Mirzabeigi, practicing in Atlanta, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003023; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; atlanta